Optimizing Curriculum Management to Improve Learning Outcomes in MTS Al-Amin Kampung Pajak - Rini Setyaningsih (CENDEKIA INDONESIA, 2025)
This study explores the process of optimizing curriculum management as a strategy to improve student learning outcomes at MTS Al-Amin Kampung Pajak. Using a qualitative descriptive method with a case study approach, data were collected through interviews, observations, focus group discussions, and document analysis involving school leaders, teachers, students, and curriculum-related documents. The findings indicate that while the school has implemented curriculum planning and execution in alignment with national standards, the process often remains administrative and lacks innovative teaching strategies. Teachers face challenges in implementing student-centered learning due to limited training, insufficient resources, and a lack of continuous professional development. Additionally, assessment practices tend to focus on summative evaluation, with minimal use of formative feedback to support student progress. Nevertheless, the study reveals strong leadership commitment and student motivation, particularly in religious subjects, which provides a foundation for curriculum enhancement. The study concludes that optimizing curriculum management requires a holistic approach, including teacher empowerment, participatory planning, data-driven evaluation, and the integration of Islamic values across subjects to create a more engaging and effective learning environment.